IMPLEMENTASI PROYEK PEMODELAN MATEMATIKA PADA KURIKULUM MERDEKA DI SEKOLAH KRISTEN IMMANUEL PONTIANAK - Yong, Benny; Wijaya, Andreas Parama; Salim, Daniel; Owen, Livia (Universitas Pattimura, 2025)
To prepare students for the rapidly evolving demands of the modern era, the Indonesian Ministry of Education, Culture, Research, and Technology introduced the Merdeka Curriculum. This curriculum provides schools and teachers with greater autonomy to design learning experiences tailored to local contexts, student potential, and individual characteristics. It emphasizes competency-based learning, integrating relevant skills and knowledge applicable to daily life and the labor market. The curriculum aims to foster creativity, critical thinking, and adaptability among students. Despite its progressive orientation, a significant challenge in its implementation is the readiness of educators. Addressing this issue requires collaborative efforts among schools, teachers, parents, communities, and the government. This community service program was designed to support teachers in implementing the Merdeka Curriculum, particularly in mathematics education. The program involved training and workshops on mathematical modeling projects aligned with the Pancasila Student Profile Strengthening Project (P5). The primary objective was to provide participants with a comprehensive understanding of curriculum implementation in mathematics and to assist them in designing student-centered project-based learning activities. The program was conducted in partnership with Immanuel Christian School, under the Kampung Bali Protestant Church Foundation in Pontianak, West Kalimantan. Overall, the mentoring activities have been highly positive, although certain materials require further refinement to ensure participants attain a more comprehensive understanding. The three strongest aspects of this program are the instructor’s deep mastery of the subject matter, the quality of the content presentation, and the organization of materials along with effective time allocation. Conversely, the aspects needing improvement are participants’ comprehension of the data analytics series, the overall relevance of the content to their needs, and their understanding of the matrix and Bayesian series